Análisis en materia de seguridad y salud ocupacional para la empresa Bio_Amazonas S.A. en la Ciudad Nueva Loja, provincia Sucumbíos - Salazar Alcivar, Mario Moises (2024)
The purpose of this research is to improve the working conditions of the staff of the company Bio_Amazonas S.A. To achieve this, existing risks in the different jobs were identified, furthermore, they were evaluated using the methodology of the National Institute of Safety and Health at Work (INSST) and the Colombian Technical Guide (GTC) 45. Once the Evaluation values were deepened, using specific methods in such a way that William W. Fine was applied for mechanical risks, identifying falls at different levels as the risk that presents a “High” Danger Degree. In the chemical risk assessment, mercaptan gases were measured, obtaining a value of the worker's daily exposure dose equal to 0.3, which concludes that risk is controlled. Applying the Biogaval-Neo method, biological risks were evaluated, obtaining values less than 8 in all biological agents, which means that it is within normal parameters. To evaluate the ergonomic risks, different methods were applied such as: “ROSA” for the Manager position which presented a risk level of 3, and “REBA” for the Maintenance Assistant and Worker positions which presented a risk level of 1. Using the questionnaire of the Ministry of Labor of Ecuador based on the ISTAS 21 Model to evaluate psychosocial risks, finding that 79.55% of the personnel presented a low psychosocial risk. Once the jobs were evaluated, the critical activities were recognized, creating a safe work manual for these activities, to improve the working conditions of both operational and administrative personnel